Fatal pulmonary embolism after degenerative lumbar spine surgery under low molecular weight heparin prophylaxis: A case report (Indian Journal of Case Reports, 2019)
Venous thromboembolism (VTE), deep vein thrombosis (DVT) and pulmonary embolism (PE) are uncommon after spine surgery. Increasing age, obesity and prolonged anaesthesia time are considered as high-risk factors for the occurrence of VTE in spinal surgeries. To prevent this fatal complication, many surgeons adopt mechanical prophylaxis like antiembolic stockinet, sequential pneumatic compression devices and early mobilization. Golden hour management of pulmonary embolism is of paramount importance. Even though PE are less commonly described in spinal surgeries, exercising caution on high-risk patients can prevent the catastrophic events. We are reporting a fatal case of pulmonary embolism following the degenerative lumbar spine surgery who succumbed to death despite the use of mechanical and pharmacologic prophylaxis (LMWH–Clexane-Enoxaparin Sodium).